Penyuluhan dan Pencegahan Penularan TB di tengah pandemi Covid-19 pada Masyarakat Kecamatan Donggo : Penyuluhan dan Pencegahan Penularan TB di tengah pandemi Covid-19 pada Masyarakat Kecamatan Donggo - hamdin; Iga Maliga (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Abstract-Tuberculosis is an infectious disease caused by bacteria (Mycobacterium tuberculosis) and most often attacks the lungs. tuberculosis is transmitted from smear positive TB patients when coughing or sneezing. Patients can spread germs into the air in the form of sputum sprinkling. Prevention of tuberculosis. This service aims to provide an understanding to the public about tuberculosis. The method used is through counseling and prevention of tuberculosis transmission in the Donggo sub-district community. The results of community service that have been carried out in the Donggo sub-district, Bima district, with the prevention of tuberculosis transmission through socialization is the right way to provide information about tuberculosis prevention and practice clean and healthy behavior habits as an effort to reduce and break the chain of tuberculosis spread in the community. The conclusion is that this infectious disease counseling has an influence on insight and increases knowledge and public awareness, especially the elderly. Keywords: Counseling on TB Transmission Prevention